PRAKTEK MANAJEMEN KINERJA DAN KINERJA ORGANISASI PADA UNIVERSITAS BATANGHARI: PERAN BUDAYA ORGANISASI SEBAGAI VARIABEL MODERATOR - Jonner Simarmata (Universitas Batanghari, 2018)
Many factors affect the relationship of management and performance both in the context of profit and non-profit organization. One of the factors is culture. Researches have shown that culture may mediate or moderate the relationship. This current research investigates the moderating role of culture on the relationship of performance management and working performance of lecturers of Batanghari University. For this, a survey was conducted by distributing a questionnaire to 36 respondents randomly selected. MRA (moderated regression analysis) was used to analyze the data. The simple regression analysis (before culture added) found that performance management practices have a significant effect on lecturer performance with 67.5% of determinant coefficient. MRA analysis (after culture added), the determinant coefficient becomes 69%, meaning there is an increase of 1.5%. F-test shows that Sig. = 0.000 is smaller than ? = 0.05, indicating that the increase is considered significant. From this analysis, it can be concluded that culture significantly moderates performance of lecturers. Then, it is suggested that culture need to be strengthened in order to improve the relationship of performance management practices and performance of lecturers.